FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEGAGALAN IBU MENYUSUI DALAM PEMBERIAN ASI EKSKLUSIF - Afrah Diba Faisal; Mayrita Syam; Siti Khoirotun Nisak; Dinda Winiastri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Exclusive breastfeeding is the primary source of nutrition for infants from birth to 6 months of age, without any additional food or drink, except for medications and vitamins recommended by healthcare professionals. Based on interviews with staff at the Indralaya Community Health Center, it was found that of the total 276 infants in the center’s service area, only 126 were exclusively breastfed. The general objective of this study was to identify the factors associated with mothers’ failure to practice exclusive breastfeeding. A cross-sectional study design was used. The study was conducted in the service area of the Indralaya Community Health Center in April 2025. The study population consisted of all mothers with infants registered at the Indralaya Community Health Center. The sample consisted of 75 participants. Purposive sampling was used. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between mothers’ knowledge (p-value: 0.002) and employment status (p-value: 0.043) and failure to achieve exclusive breastfeeding. It is recommended that the Community Health Center provide education and information on exclusive breastfeeding, empower mothers starting from pregnancy to improve their knowledge regarding breastfeeding preparation, and involve family members or husbands to support the mother’s breastfeeding preparation process and the breastfeeding period.Keywords: Failure to Exclusively Breastfeed, Maternal Knowledge, Employment Status.